2019
DOI: 10.26434/chemrxiv.7613042.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Nature of Halide-Water Interactions: Insights from Many-Body Representations and Density Functional Theory

Abstract: <div> <div> <div> <p>Interaction energies of halide-water dimers, X<sup>-</sup>(H<sub>2</sub>O), and trimers, X<sup>-</sup>(H<sub>2</sub>O)<sub>2</sub>, with X = F, Cl, Br, and I, are investigated using various many-body models and exchange-correlation functionals selected across the hierarchy of density functional theory (DFT) approximations. Analysis of the results obtained with the many-body models demonstrates t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 92 publications
2
44
0
Order By: Relevance
“…It should be noted that our previous analyses showed that, among the existing functionals, ωB97M-V consistently provides the closer agreement with CCSD(T) reference data for molecular interactions in aqueous systems. 69,71,81,82,111 As expected from the analysis of the correlation plots in Fig. 2 A direct probe of the multidimensional 2B energy landscape is provided by the second virial coefficient,…”
Section: Many-body Decompositionmentioning
confidence: 67%
See 1 more Smart Citation
“…It should be noted that our previous analyses showed that, among the existing functionals, ωB97M-V consistently provides the closer agreement with CCSD(T) reference data for molecular interactions in aqueous systems. 69,71,81,82,111 As expected from the analysis of the correlation plots in Fig. 2 A direct probe of the multidimensional 2B energy landscape is provided by the second virial coefficient,…”
Section: Many-body Decompositionmentioning
confidence: 67%
“…1 can be correctly represented in terms of classical many-body polarization as described in Section 2.1. In this context, it should be noted that previous studies of manybody effects in aqueous systems indicated that an explicit representation of 3B energies is necessary to guarantee an accurate description of structural, thermodynamic, dynamical and spectroscopic properties of water 75,[109][110][111] as well as halide-water 69,79,[81][82][83][84][85] and alkali-metal ion-water 71,80,86 interactions in the gas phase and in solution. In particular, it was found that significant error cancellation between different terms of the MBE affects the performance of common force fields and DFT models for water.…”
Section: Many-body Decompositionmentioning
confidence: 99%
“…1 to develop TTM-nrg and MB-nrg PEFs for halide-water, 82,83 alkali-metal ion-water, 84,85 and carbon dioxide-water systems, 86 which have been employed in computer simulations of various aqueous systems. [94][95][96][97][98][99][100][101] While both TTM-nrg and MB-nrg PEFs rely on MB-pol to describe water-water interactions, they differ in the functional forms adopted to represent solute distortions and solute-water interactions. In the TTM-nrg PEF, the CH 4 1B term is represented by a functional form similar to those used in common force fields, which is expressed in Eq.…”
Section: Ttm-nrg and Mb-nrg Functional Formsmentioning
confidence: 99%
“…38 Different functionals may describe anion-water and cation-water interactions with signif-icantly different accuracy. 24 GGAs appear to already adequately reproduce the structure of halide ions such as iodide. 61 But the accuracy of SCAN when applied to anions should be tested in future work.…”
Section: Structural Analysismentioning
confidence: 99%